1 Why Neighborhoods? The Neighborhood in Archaeological Theory and Practice. Issue 1 (4th July 2019) - Pacifico, David; Truex, Lise A.
ABSTRACT: This chapter introduces the central themes in this volume and articulates those themes with previous approaches. Neighborhoods in this volume are integrative socio‐spatial groups between the household and the settlement that are found in urbanizing landscapes. Previous theorizations of neighborhoods constrain them to specific populations or forms of sociality. Our cases show that the fundamental aspects of these theorizations (intermediate, distinct, cohesive, nested) can endure while population, morphology, and temporality vary. Neighborhood studies are presented as complementary to household, community, and urban/peri‐urban studies, while attention is drawn to the diversity of forms neighborhoods take and diversity of themes neighborhoods help scholars address.